Perkembangan Livelihood Menongkah Suku Duano menjadi Festival Budaya Masyarakat Indragiri Hilir - Vitasari; Viktor Amrivo; Khodijah Ismail; T.Ersty Yulikasari (Jurnal Ekologi, Masyarakat dan Sains, 2023)
Menongkah activities initially became the main livelihood of the Duano Tribe to fulfill their daily needs due to environmental degradation which caused bio-physical changes which caused the Duano Tribe to no longer be able to sail the ocean to catch fish so they settled by catching cockle (Anadara granosa) which abound in mud areas Indragiri Hilir. Menongkah activities are carried out using a tongkah board as a pedestal to catch cockles on the mud. Tongkah boards are used as a form of technological adaptation by the Duano Tribe to the muddy bio-physical environment. Livelihood with menongkah has been carried out for generations by the Duano people, so the culture of menongkah of the Duano tribe is a legacy that needs to be preserved. With government support, the menongkah activity is made one of the annual cultural festivals included in the Riau Province cultural tourism calendar. The environment which is the habitat of the cockle (Anadara granosa) needs to be maintained so that the existence of the Duano Tribe's livelihood and culture in menongkah is maintained.